A Predicament on the Use of English Language in International Accounting Classes: Tension between Market and Ideal Education - Ari Kamayanti; L Agustina; R Damayanti (Universitas Muhammadiyah Jakarta, 2026)
The article highlights the challenges faced by lecturers and students in international accounting classes, where English is not their first language, due to the complexity of accounting terms and techniques. Students must acquire understanding of terms, regulation, and even a calculative approach to solving accounting problems. A descriptive method was used to investigate the level of English use in accounting classes as well as the language problems encountered by students. A questionnaire with closed and opened questions were employed to collect data. It is discovered that students felt both they and the lecturers do not always have sufficient ability to communicate effectively in English. As a result, Indonesian lecturers felt compelled to deliver lessons in Bahasa Indonesia to ensure that the materials taught are understood by the majority of Indonesian students in international classes. Foreign students who have already struggled with English as a second language will find it even more difficult to keep up with international classes if this is done. The article explores how English is utilized as foreign language in the accounting learning process and relates it to the ideals of education, as an issue that is rarely raised. The institution must reconsider the concept of “internationalization” and devise a program to relieve the tension between the international class market and the ideal accounting education.